Peculiarities of Involving a Specialist in the Preparation and Conduct of Interrogation at the Stage of Pre-Trial Investigation - Rodiuk, O. V. (Вісник Харківського національного університету внутрішніх справ, 2025)
The article provides a comprehensive analysis of the legal and practical framework for involving specialists in interrogation at the pre-trial investigation stage. It is noted that in the current conditions of crime investigation, the requirements for the quality of information collected and the objectivity of evidence are increasing. This necessitates the involvement of specialists from various fields of knowledge – criminologists, psychologists, doctors, linguists, teachers and others – with a view to improving the effectiveness of investigative actions. Specialists not only provide technical and methodological support for interrogation, but also contribute to a deeper understanding of the individual characteristics of the person being interrogated, which allows for adaptation of communication tactics and minimisation of the risks of obtaining distorted information. The specifics of legal regulation of the participation of specialists, including their procedural status, powers and responsibilities, are considered. The author analyses the stages of interaction between an investigator and a specialist: from preparation for interrogation to recording its results. Particular attention is paid to the impact of the qualifications and level of competence of specialists on the reliability, completeness and evidentiary value of the information obtained. It is emphasised that taking into account the psychophysiological and psychological characteristics of the person being interrogated helps to reduce pressure, increase the informative value of testimony and respect for human rights. The article substantiates the importance of an interdisciplinary approach in pre-trial proceedings based on the interaction of forensic science, legal psychology, psychophysiology and other related sciences. The methodological problems and organisational features of involving specialists, as well as the criteria by which the expediency of their participation is determined, are considered. It is concluded that integration of expert knowledge into investigative practice is a relevant direction of increasing the efficiency of crime detection and strengthening the evidence base in criminal proceedings.